PROPOSAL FOR A SACRAMENTAL THEOLOGY TO THE SYRO-MALABAR CHURCH WITHIN THE FRAMEWORK ‘CONTEXT-LITURGY-ETHICS - Vazhappilly, Bilju F. (Asian Horizons, 2015)
Often we hear the plea for a theology emerging from the ecclesial, liturgical and cultural contexts of a Church sui iuris. In the field of sacramental theology too the case is not different. In reference to the present situation of the Syro-Malabar Church such this is a need of the time. Much research related to this has not been done. This article makes a humble attempt to develop a sacramental theology without losing one’s own ecclesial and liturgical traditions in which one is born and brought up. After explicating a renewed understanding of the term sacrament and the mediatory role of the Church, we formulate the proposed sacramentaltheology of the Syro-Malabar Church today within the framework of context-liturgy-ethics. Such a way of doing sacramental theology will be done through a theological dialogue with the cultural context, the liturgical ethos and the pastoral concerns of the Syro-Malabar Christians today.